Histopathological changes in some tissues of Tigris river fishes, exposed to petroleum hydrocarbons, Baghdad city: Nahla Taleb Mansoor1, Enam Bader Faleh2, Lauya Mohamad Abas1, Kasim Rethaw Asmer1 and Mustafa Jawad Jalil1 - Mansoor, Nahla Taleb (The Iraqi Journal of Veterinary Medicine, 2016)
During the period between January till December 2012, a total of 119 fish samples were collected and examined from Tigris River between Al-Jadiriya Bridge and Al-Zaafaraniya region in two stations, the first station was located under Al-Jadiriya bridge and the second station was located at Al-Zaafaraniya region before Diayla river in order to know the effects of petroleum hydrocarbons in the tissues of the examined fishes. Fish samples belonged to (16) species (Acanthobrama marmid, Albernus caeruleus, Aspius vorax, Barbua belayewi, B. grypus, B. xanthopterus, Carassius carassius, Carasobarbus luteus, Cyprinion macrostomum, Chondrostomua regium, Gara ruffa, Heteropneustes fossilis, Leuciscus cephalus, Liza abu, Mystus pelusius and Tilapia zillii). The histopathological examination included 44 specimens from the internal and external organs of Chontrostoma regium in order to examine the histopathological changes in some organs like (gills, muscles, kidney, liver and spleen). The results revealed congestion, edema, separating, severe vacuolation and dilation of gill secondary lamella, while muscle samples showed mild hyalinization, infiltration of mononuclear cells and fragmentation. The kidney showed hydropic degeneration, necrosis changes, hyperplastic of melanomacrophages, severe dilation of blood vessels with cellular swelling of renal tubule epithelial lining and depletion of hemopoiotic tissues. Severe dilation and congestion of blood vessels and sinusoid, nucleopleomorphism were noticed with nucleomegalocytic of hepatocytes, hemorrhagic with mineral deposition in hepatic parenchyma. Lymphoid depletion in white pulp and hemopoitic tissues, congestion of red pulp, severe hyperplasia were noticed with dilation of splenic tissues. Water samples from Tigris river were analyzed for measuring the level of petroleum hydrocarbons in water and appeared that the pollution 0.0048 mg/L in Al-Jadiriya station and 0.0674 mg/L in Al-Zaafaraniya station.